Detection of Lactobacillus delbrueckii subsp. bulgaricus and Streptococcus thermophilus in Inactivated Fermented Milk Using Fluorescence Quantitative Loop-Mediated Isothermal Amplification - Shuaikang Zhou; Lianxia Hu; Yuling Xue; Dong Zhang; Baokuo Song; Mengyang Wang; Qingbin Yuan; Yibing Ning; Shijie Wang (Journal of Food Quality)
Currently, no effective method exists to detect and monitor fermentation probiotics and evaluate the quality of inactivated fermented milk. Therefore, in this study, a fluorescence quantitative loop-mediated isothermal amplification (FQ-LAMP) method was developed to detect Lactobacillus delbrueckii subsp. bulgaricus and Streptococcus thermophilus. The specificity of LAMP primers for L. bulgaricus and S. thermophilus was verified using S-type amplification curves and a single peak at approximately 88.568°C and 83.704°C of the melting curves, respectively. The lowest quantification limits of FQ-LAMP for the two strains in inactivated fermented milk were 8.1 × 103 CFU/g (170 fg/μL) and 6.8 × 103 CFU/g (170 fg/μL), respectively. FQ-LAMP was used to analyse 40 inactivated fermented milk samples from six randomly selected brands. The logarithmic concentration of S. thermophilus in all products was between 7.482 and 8.936. The logarithmic concentration of L. bulgaricus ranged from 4.590 to 8.277, with no detectable L. bulgaricus in three samples. FQ-LAMP has the potential as a rapid, specific, and accurate method for detecting and monitoring L. bulgaricus and S. thermophilus in inactivated fermented milk during their shelf life.